2016
DOI: 10.1002/anie.201607600
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Synthesis of Methanol: Understanding the Requirements for an Industrial Catalyst for the Conversion of CO2

Abstract: The hydrogenation of CO to methanol is a potential process for the sustainable production of synthetic liquid fuels. The Cu/ZnO catalyst employed for this reaction has been studied extensively for many years, and recent progress now has the potential to turn it into a prototype for complex promotional interactions in heterogeneous catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 32 publications
1
68
0
Order By: Relevance
“…It is concluded that, to date, the catalysts used in the carbon dioxide hydrogenation reactiong ive aw ide product distribution, which reduces the specifics electivity to lower olefins.M ore efforts are needed to reach better control of the C/H surface ratio and interactions within the functionalities of the catalyst, as well as understanding the reaction mechanism and avoiding deactivation. [12] However,m ethanol is nowadays also obtained from CO 2 .F or example, Carbon Recycling International( CRI) developed the world's first commercialC O 2 to methanolp lant in Iceland. Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that, to date, the catalysts used in the carbon dioxide hydrogenation reactiong ive aw ide product distribution, which reduces the specifics electivity to lower olefins.M ore efforts are needed to reach better control of the C/H surface ratio and interactions within the functionalities of the catalyst, as well as understanding the reaction mechanism and avoiding deactivation. [12] However,m ethanol is nowadays also obtained from CO 2 .F or example, Carbon Recycling International( CRI) developed the world's first commercialC O 2 to methanolp lant in Iceland. Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…). Although many efforts were made to develop catalysts for optimized CO 2 hydrogenation to methanol, the industrially applied Cu‐based catalyst still dominates CO 2 hydrogenation due to its outstanding performance , , , .…”
Section: Co2hydrogenation To Methanolmentioning
confidence: 99%
“…Therefore, by the use of biomass‐derived CO 2 or recycled CO 2 from industrial plants such as coal‐fired power plants or steel mill plants, methanol synthesis can contribute to CO 2 mitigation of greenhouse gas concentrations in the atmosphere . Thus, topics like emission‐to‐liquid or power‐to‐fuel , , where CO 2 emissions can be utilized using renewable energy, are investigated intensively and several pilot plants have already been built . The high energy demand of converting the thermodynamically very stable molecule CO 2 is the most challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…The Cu/ZnO based catalysts are widely applied on various catalytic reactions involving synthesis of alcohols . Studies on the phases of Cu‐containing hydroxycarbonates revealed that some precursor phases play important role for the catalytic performance .…”
Section: Introductionmentioning
confidence: 99%
“…The Cu/ZnO based catalysts are widely applied on various catalytic reactions involving synthesis of alcohols. [1][2][3][4][5][6][7][8] Studies on the phases of Cu-containing hydroxycarbonates revealed that some precursor phases play important role for the catalytic performance. [9][10][11][12][13] The Zn-doped malachite, (Cu 1À x ,Zn x ) 2 (OH) 2 CO 3 , possess homogeneous microstructure, well dispersion of Cu 2 + and Zn 2 + at an atomic level, enhanced metal-oxide interaction after calcination, stability against sintering and high specific surface area and is considered as an effective precursor for industrial Cu/ZnO catalyst.…”
Section: Introductionmentioning
confidence: 99%